(untitled) (Transport systems and technologies, 2023)
The article examines the issue of the chassis system of a high-speed electric train with body inclination and a vibration recovery system. The advantages of using an electromechanical shock absorber over hydraulic, pneumatic and similar systems are described. The authors considered the main characteristics of the DC electromechanical shock absorber. The main overall parameters of the shock absorber were presented. Attention is paid to the relevance of using an electromechanical shock absorber of a linear type, in comparison with analogues, including the ability to recover energy. Attention is drawn to the structure of the DC electromechanical shock absorber. The functional control scheme of the electromechanical shock absorber is considered and the control algorithm is described. The calculation areas of the parameters of the electromechanical shock absorber are determined. A 3D model of an electromechanical shock absorber in the Ansys Electronics software environment is presented. A finite-element mesh was built for further calculations of the magnetic field and inductance. In the article, attention is paid to the calculation of the magnetic field in the most intense mode. A picture of the shock absorber’s magnetic field at the maximum working clearance was obtained and interim results were discussed. The results of calculating the inductance depending on the operating gap of the shock absorber are presented. Conclusions were made based on the results of calculations of magnetic and electrical parameters of an electromechanical shock absorber based on a linear direct current motor.